2021
DOI: 10.1101/2021.01.08.20248932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy of propolis as an adjunct treatment for hospitalized COVID-19 patients: a randomized, controlled clinical trial

Abstract: Among candidate treatment options for COVID-19, propolis, produced by honey bees from bioactive plant exudates, has shown potential against viral targets and has demonstrated immunoregulatory properties. We conducted a randomized, controlled, open-label, single center trial, with a standardized propolis product (EPP-AF) on hospitalized adult COVID-19 patients. Patients received standard care plus propolis at an oral dose of 400mg/day (n=40) or 800mg/day (n=42) for seven days, or standard care alone (n=42). Sta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In the present study, a promising result was found when the median LOS further decreased to 4 days in the AM group, which differed signi cantly from the NAM group, which had an average LOS of 7 days. On the other hand, it is possible to hypothesize that NAM itself was effective in reducing LOS when compared to previous studies [27,28]. This result is probably due to mechanical hygiene of the oral and oropharynx cavities.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In the present study, a promising result was found when the median LOS further decreased to 4 days in the AM group, which differed signi cantly from the NAM group, which had an average LOS of 7 days. On the other hand, it is possible to hypothesize that NAM itself was effective in reducing LOS when compared to previous studies [27,28]. This result is probably due to mechanical hygiene of the oral and oropharynx cavities.…”
Section: Discussionmentioning
confidence: 65%
“…Data regarding the mean time of hospitalization due to COVID-19 vary between geographic areas, but 14 days was found to be a reliable LOS time for patients in hospitals in China [27]. In a recent study [28] was described a median hospital stay period of 12 days in Brazil, which decreased to 6 to 7 days, depending on the concentration of propolis intervention used by the patients. In the present study, a promising result was found when the median LOS further decreased to 4 days in the AM group, which differed signi cantly from the NAM group, which had an average LOS of 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…A Brazilian Randomized control trial reported that treating hospitalized COVID-19 patients with a single oral daily dose of nonalcoholic preparation non-alcoholic preparation was associated with significant reductions in the length of hospital stay (LOS) and renal injury. Propolis treatment was not associated with a decrease in the need for oxygen therapy [7].…”
Section: Anti-covid-19 Effects Of Propolismentioning
confidence: 83%
“…COVID-19 showed that the length of hospital stay in Brazil ranged from 12 to 7 days, depending on the concentration of propolis used by patients (Silveira et al, 2021). In our study, the hospitalization rate decreased from an average of 8.2 days in the placebo group to 4.6 days in the group receiving propolis syrup with H. niger L. This reduction in the rate of admission from propolis syrup along with H. niger L. causes a significant increase in arterial blood oxygen pressure on Day 6 (Kosari et al, 2021;Silveira et al, 2021). Propolis in clinical trial studies in the asthmatic model, which is double-blind, also increased spirometry parameters and decreased asthma attacks (Mirsadraee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%